2009
DOI: 10.1080/03055690802648531
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of young learners’ foreign language competence in three Eastern European countries

Abstract: The central part of the article focuses on an international project involving empirical research into assessment of young learners' foreign language competence in Slovenia, Croatia and the Czech Republic. With the help of an adapted questionnaire, we collected data from a nonrandom sample of primary and foreign language teachers who teach foreign languages at the primary level in these countries.The research shows that English as a foreign language is taught mostly by young teachers either primary specialists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 3 publications
3
14
0
Order By: Relevance
“…Although some studies reported teacher satisfaction and positive attitudes towards alternative assessment (Yu-Ching, 2008;Brumen et al, 2009;Brown et al, 2009;Alkharusi, Aldhafri, Alnabhani, & Alkalbani, 2012;Gonzales & Aliponga, 2012;Tangdhanakanond & Wongwanich, 2012), most studies on primary school teachers' attitudes towards assessment came to the conclusion that most teachers' attitudes are at an average or low level (Watt, 2005;Yang, 2007;Metin, 2011;Ghazali, Yaakub, & Mustam, 2012). The inconsistency in results might be related to the fact that in some studies candidates were primary and secondary school teachers.…”
Section: Related Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies reported teacher satisfaction and positive attitudes towards alternative assessment (Yu-Ching, 2008;Brumen et al, 2009;Brown et al, 2009;Alkharusi, Aldhafri, Alnabhani, & Alkalbani, 2012;Gonzales & Aliponga, 2012;Tangdhanakanond & Wongwanich, 2012), most studies on primary school teachers' attitudes towards assessment came to the conclusion that most teachers' attitudes are at an average or low level (Watt, 2005;Yang, 2007;Metin, 2011;Ghazali, Yaakub, & Mustam, 2012). The inconsistency in results might be related to the fact that in some studies candidates were primary and secondary school teachers.…”
Section: Related Literaturementioning
confidence: 99%
“…However, research has shown that most primary school teachers realize the importance of alternative assessment in improving teaching and learning (Yang, 2007;Yu-Ching, 2008;Brumen, Cagran, Coombe, Edmonds, Heckstall-Smith, & Fleming, 2009;Brown, Lake, & Matters, 2009). In a survey of New Zealand primary school teachers' conceptions of alternative assessment, Brown (2004) found that teachers agreed that assessment improves teaching and learning and makes schools accountable.…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…At the end of compulsory education, children who began learning English in grade 3 should have reached level A2 (in accordance with the Common European Framework for Languages); those who began learning English in grade 8 will have achieved level A1. Many children begin learning a FL in lower grades, in optional extra classes for which fees are payable (Brumen et al, 2009). However, as indicated in the study, in Turkey, teaching EFL has some problems because of the other teachers (science, mathematic, music teachers, etc…but not English teachers) who teach EFL in some primary schools.…”
Section: Discussionmentioning
confidence: 94%
“…In Hungary, similarly to the international arena (e.g., Brumen, Cagran, & Rixon, 2009;Butler, 2009aButler, , 2009bButler, , 2015Edelenbos & Kubanek-German, 2004;Peng & Zheng, 2016;Wilden & Porsch, 2016) research on teachers' assessment practices is fairly limited. A few studies, however, explored classroom assessment.…”
Section: Literature Reviewmentioning
confidence: 99%